Solution structure of the zinc finger domain of human RNF144A ubiquitin ligase - Miyamoto, Kazuhide (Protein Sci, 2020)
RNF144A is involved in protein ubiquitination and functions as an ubiquitin‐protein ligase (E3) via its RING finger domain (RNF144A RING). RNF144A is associated with degradation of heat‐shock protein family A member 2 (HSPA2), which leads to the suppression of breast cancer cell proliferation. In this study, the solution structure of RNF144A RING was determined using nuclear magnetic resonance. Moreover, using a metallochromic indicator, we spectrophotometrically determined the stoichiometry of zinc ions and elucidated that RNF144A RING binds two zinc atoms. This structural analysis provided the position and range of the active site of RNF144A RING at the atomic level, which contributes to the creation of artificial RING fingers having the specific ubiquitin‐conjugating enzyme (E2)‐binding capability.